DEDICATIONS IN PRUSSIAN BOOKS AS CULTURAL MEMORIALS TO FAMOUS FOREIGN DEFENDERS OF THE LITHUANIAN LANGUAGE - KOŽENIAUSKIENĖ, REGINA (Knygotyra, 2015)
The people called (with certain reservations) foreigners in this article are dedicators and dedicatees of Prussian books, men of culture, literature and science, who did not write in Lithuanian, but only in German, Latin or other languages. The main criterion for calling them foreigners is not their origin or nationality but their language. They were not the creators of Lithuanian writings, but rather promoters and supporters who helped to organise the preparation and publication of Lithuanian books. They organised a seminar of the Lithuanian language at Konigsberg University, showed sincere interest in the live Lithuanian language and studied it as a precious item, i.e. one of the oldest Indo-European languages, spreading the knowledge about it to the enlightened public in other countries. Most importantly, they distinguished themselves as defenders of the Lithuanian language. Therefore it is quite understandable why the names of foreign dedicators and dedicatees, mostly prominent Prussian Germans – high rank officials, renowned poets and scientists, rectors of Konigsberg academy, professors of rhetoric who rebuffed the despisers of the Lithuanian nation and its language – should be treasured. The focus of the article is on Ludwig Rhesa’s dedication to the German baron Wilhelm von Humboldt in the first edition of Donelaitis “The Seasons” (1818), however, it is presented in a historical cultural context: the earlier or later works of other foreign dedicators and dedicatees are mentioned. One of the later items is an original dedication delivered by Franz Tetzner in the late 19th century at the memorial stone to Donelaitis in Lazdynėliai. The latter ceremonial rhetorical work which was communicated orally (not only in written form) happens to be outside the boundaries of this research, because this dedication was not published in a Prussian book, but in the newspaper “Lietuwiszka Zeitunga“. That being said, the work in question is mentioned because of its direct relationship to Donelaitis, the disclosure of his phenomenon, as well as because of dedications as a continuing rhetorical tradition in verse and the final statement about the position of the Lithuanian language in Donelaitis’ native land. The study aims to show the contribution of foreign dedicators and dedicatees to the Lithuanian language in the following aspects: firstly, to assess the dedications devoted to the authors and compilers of Lithuanian books as deep imprints of the defenders of the Lithuanian language and as works providing valuable material for better acquaintance with the authors’, including Rhesa, aims and motives. Secondly, to look at these dedications as monuments of high rhetorical culture.